Association of smoking with amyotrophic lateral sclerosis: A systematic review, and meta-analysis, including dose-response analysis - Kihun Kim+; Dai Sik Ko+; Jin-Woo Kim; Dongjun Lee; Eunjeong Son; Hyun-Woo Kim; Tae-Jin Song+; Yun Hak Kim (Tobacco Induced Diseases)
Introduction Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disorder primarily affecting the voluntary motor nervous system. Several observational studies have provided conflicting results regarding the association between smoking and ALS. Therefore, Therefore, our objective was to investigate this association through systematic review, meta-analysis, and dose-response analysis.